The effect of irradiance on the carbon balance and tissue characteristics of five herbaceous species differing in shade-tolerance - Pons, Thijs L. (Frontiers Media S.A., 2014)
The carbon balance is defined here as the partitioning of daily whole-plant gross CO(2) assimilation (A) in C available for growth and C required for respiration (R). A scales positively with growth irradiance and there is evidence for an irradiance dependence of R as well. Here we ask if R as a fraction of A is also irradiance dependent, whether there are systematic differences in C-balance between shade-tolerant and shade-intolerant species, and what the causes could be. Growth, gas exchange, chemical composition and leaf structure were analyzed for two shade-tolerant and three shade-intolerant herbaceous species that were hydroponically grown in a growth room at five irradiances from 20 μmol m(−2) s(−1) (1.2 mol m(−2) day(−1)) to 500 μmol m(−2) s(−1) (30 mol m(−2) day(−1)). Growth analysis showed little difference between species in unit leaf rate (dry mass increase per unit leaf area) at low irradiance, but lower rates for the shade-tolerant species at high irradiance, mainly as a result of their lower light-saturated rate of photosynthesis. This resulted in lower relative growth rates in these conditions. Daily whole-plant R scaled with A in a very tight manner, giving a remarkably constant R/A ratio of around 0.3 for all but the lowest irradiance. Although some shade-intolerant species showed tendencies toward a higher R/A and inefficiencies in terms of carbon and nitrogen investment in their leaves, no conclusive evidence was found for systematic differences in C-balance between the shade-tolerant and intolerant species at the lowest irradiance. Leaf tissue of the shade-tolerant species was characterized by high dry matter percentages, C-concentration and construction costs, which could be associated with a better defense in shade environments where leaf longevity matters. We conclude that shade-intolerant species have a competitive advantage at high irradiance due to superior potential growth rates, but that shade-tolerance is not necessarily associated with a better C-balance at low irradiance. Under those conditions tolerance to other stresses is probably more important for the performance of shade-tolerant species.